Berger, Monica (audio interview #5 of 6) - Berger, Monica (1891 - ); Briegel, Kaye, interviewer
INTERVIEW DESCRIPTION - This interview was conducted in Berger's home in Leisure World in Seal Beach. 8/25/1979